Evolutionary trajectory of bacterial resistance to antibiotics and antimicrobial peptides in Escherichia coli - Feiyu Yu; Dejuan Wang; Haijie Zhang; Zhiqiang Wang; Yuan Liu (mSystems)
ABSTRACT The global crisis of antimicrobial resistance poses a major threat to human health, underscoring the urgency of developing new antibacterial strategies. Antimicrobial peptides (AMPs) are promising alternatives to antibiotic therapy, yet potential microbial resistance is of great concern. Resistance is often accompanied by fitness costs, which may in turn influence the spread of drug-resistant bacteria and their susceptibility to other antimicrobial agents. Herein, we investigate the evolutionary trajectory of bacterial resistance to antibiotics and AMPs in Escherichia coli, and evaluate the fitness costs and collateral sensitivity of drug-resistant strains. We reveal that E. coli develops resistance to antibiotics, particularly ciprofloxacin and kanamycin, at a notably faster rate than to AMPs. Moreover, antibiotic-evolved strains exhibit slightly higher fitness costs than AMP-evolved bacteria, primarily manifested in reduced bacterial growth and swimming motility. Notably, we demonstrate that trimethoprim-resistant E. coli, with mutations in thyA gene, displays enhanced susceptibility to pexiganan, as evidenced by both in vitro and in vivo studies. Overall, our findings shed new insights for the clinical deployment of AMPs and propose innovative therapeutic strategies for combating antibiotic-resistant bacterial infections.IMPORTANCEThe global spread of antimicrobial resistance necessitates the development of innovative anti-infective strategies. Antimicrobial peptides (AMPs) represent promising alternatives in the post-antibiotic era. By monitoring the evolutionary trajectory of bacterial resistance to eight antibiotics and ten AMPs in Escherichia coli, we demonstrate that E. coli exhibits slower emergence of resistance against AMPs compared with antibiotics. Additionally, these antibiotic-resistant strains incur significant fitness costs, particularly in bacterial growth and motility. Most importantly, we find that some antibiotic-resistant strains show collateral sensitivity to specific AMPs in both in vitro and animal infection models, which is conducive to accelerating the development of AMP-based antibacterial treatment.